Epidemiology of Methicillin-Susceptible Staphylococcus aureus in a Neonatology Ward. (20th August 2015) - Achermann, Yvonne; Seidl, Kati; Kuster, Stefan P.; Leimer, Nadja; Durisch, Nina; Ajdler-Schäffler, Evelyne; Karrer, Stephan; Senn, Gabriela; Holzmann-Bürgel, Anne; Wolfensberger, Aline; Leone, Antonio; Arlettaz, Romaine; et al.
Abstract : OBJECTIVE: In-hospital transmission of methicillin-susceptible Staphylococcus aureus (MSSA) among neonates remains enigmatic. We describe the epidemiology of MSSA colonization and infection in a 30-bed neonatal ward. DESIGN: Multimodal outbreak investigation SETTING: A public 800-bed tertiary care university hospital in Switzerland METHODS: Investigations in 2012–2013, triggered by a MSSA infection cluster, included prospective MSSA infection surveillance, microbiologic screening of neonates and environment, onsite observations, and a prospective cohort study. MSSA isolates were characterized by pulsed-field gel electrophoresis (PFGE) and selected isolates were examined for multilocus sequence type (MLST) and virulence factors. RESULTS: Among 726 in 2012, 30 (4.1%) patients suffered from MSSA infections including 8 (1.1%) with bacteremia. Among 655 admissions in 2013, 13 (2.0%) suffered from MSSA infections including 2 (0.3%) with bacteremia. Among 177 neonates screened for S. aureus carriage, overall 77 (44%) tested positive. A predominant PFGE-1-ST30 strain was identified in 6 of 30 infected neonates (20%) and 30 of 77 colonized neonates (39%). This persistent clone was pvl -negative, tst -positive and belonged to agr group III. We found no environmental point source. MSSA carriage was associated with central vascular catheter use but not with a particular midwife, nurse, physician, or isolette. Observed healthcare worker behavior may have propagated transmission via hands and fomites. Despite multimodal interventions, clonal transmission and colonization continued and another clone, PFGE-6-ST5, became predominant. CONCLUSIONS: Hospital-acquired MSSA clones represent a high proportion of MSSA colonization but not MSSA infections in neonate inpatients. In contrast to persisting MSSA, transmission infection rates decreased concurrently with interventions. It remains to be established whether eradication of hospital-acquired MSSA strains would reduce infection rates further. Infect. Control Hosp. Epidemiol. 2015;36(11):1305–1312